Health Prevention Intervensions for the Control of Hypertension: a Systematic Review - Anggi Asri Rusliana Dewi; Dumilah Ayuningtyas (Journal of Social Research, 2023)
Hypertension is a major cardiovascular risk factor (CVD), contributing significantly to the worldwide burden of cardiovascular disease and disability, but its control remains an unmet challenge for public health systems. WHO estimates that there are 1.28 billion adults (aged 30-79 years) in the world with hypertension and an estimated 46% of them do not know they suffer from hypertension because hypertension is the silent killer. This Systematic Review aims to identify and analyze preventive health interventions for hypertension control, as well as promotional efforts that can be done to reduce the prevalence of hypertension at the global level. This study uses the Systematic Review method to search for articles based on several databases, namely Scopus, EMBASE, ScienceDirect, and PubMed on May 12, 2023. Search results with keywords hypertension, health prevention interventions, hypertension health promotion, hypertension control, decreased prevalence of hypertension. After being filtered based on suitability with the title and research objectives, relevant research articles were obtained, the full text was free and the publication year 2018-2023 produced 8 articles. The results of this study are several efforts to prevent the increase in the prevalence of hypertension, namely by promoting health to carry out physical activity, reducing stress levels, balanced diet and nutrition, maintaining ideal body weight, reducing salt consumption, not smoking and reducing cigarette smoke, avoiding alcoholic beverages, and lifestyle education interventions through education and counseling. Further research is needed regarding the most effective interventions for the prevention and control of hypertension.